PENGARUH IN HOUSE TRAINING DAN PENGETAHUAN DASAR KEPENDIDIKAN TERHADAP KEMAMPUAN GURU MENERAPKAN STRATEGI KOPERATIF LEARNING - Alhafif Syahputra (Universitas Islam Negeri Sumatera Utara Medan, 2021)
As a learning strategy that is highly recommended for a teacher, cooperative learning strategies requere knowledge and skills to use them. In order for teachers to master well, training is requered along with its implementation. In House Training model that is carried out while the teacher is carrying out his/her job as a teacher. Basic education knowledge is the knowledge needed by a teacher to carry out his duties as a teacher. Research on increasing the ability of teachers to apply cooperative learning strategies is designed as an experimental study. Implemented in Pematangsiantar city among private Madrasah Tsanawiyah tachers with 32 teachers. The research results show that : 1) there are differencies in the ability of teachers to apply cooperative learning strategies between those who have high basic knowledge of education and those who have low basic educational knowledge, 2) there are differencies in the ability of teachers to apply cooperative learning strategies between those guided by the role flaying method and the discussion method, and 3) there is an interaction between basic education knowledge and methods in increasing the ability of teachers to apply cooperative learning stategies. Keywords : In House Training, basic educational knowledge, cooperative learning.